Workload Analysis in Determining the Needs Analysis of the Number in Education Personnel at XYZ University Yogyakarta - Sutoyo, Sutoyo; Syari'udin, Akhmad; Siswanti, Yuni; Yulianti, Retno (RSF Conference Series: Business, Management and Social Sciences, 2021)
Background – XYZ University in Yogyakarta is one of the new state universities which, is currently preparing to enter the Public Service Agency in determining the number of technicians to be distributed to work units. There is no standard provision until now. The actual condition so far is a gap in the number of technicians in several work units. Every team has an excess number of Education Personnel, but in other work units, they experience a shortage. This clear interferes with the tendons' expected performance of the tendons, thus impacting the work unit. Research Purpose - Based on these conditions, this study analyzed the need for educational personnel based on workload analysis. Research Methodology- The study conducted in several units with resource determination method used purposive samplings (specific criteria) at XYZ University in Yogyakarta. Methods of data collection with interviews and documentation. Sources of data in the form of primary and secondary data. The results of this study are expected to be useful for institutional leaders regarding the proportional number of education personnel needed in each work unit. Research Result /Contribution – This research shows that some excess human resources and units lack human resources. However, when viewed from the job description, it turns out that several jobs are routinely low on a daily or weekly basis. But there is a relatively high need for hours in annual activities so, that the workload is uneven. The management needs to be considered the number of when analyzing employees in each work unit. The results provide an overview to the management of XYZ University in planning employee needs in the future period.